Women and Sexually Transmitted Diseases in Soviet Society: Based on the Materials of the Medical Reports of the Dispenser for Skin and Venereal Diseases of the Daugavpils City in Latvian USR (1953–1964) - Krylova, Iveta (Acta humanitarica academiae Saulensis, 2025)
In the Soviet period during the “Khrushchev thaw” (1953–1964), in the territory of Latvian USR, social and economic problems and decline of moral values in Soviet society became the foundation to the spread of venereal (sexually transmitted) diseases – trichomoniasis, gonorrhea, and syphilis – among women and their family members. In Soviet society exposed to risk were not only women with pronounced marginal behavior (women with alcohol addiction, women of deviant sexual behavior), single women, but also housewives, married women with husbands who did not avoid casual sexual behavior. Social and economic problems, low wages, shortage of goods made women available for casual relationships for reward. In Soviet society, not only women infected with sexually transmitted diseases were stigmatized, but also the people with whom they had contact, their families, and their children. The paper reveals and analyzes the statistics on the prevalence and incidence of three types of venereal diseases – trichomoniasis, gonorrhea and syphilis – and the nature of incidents between 1953 and1964 among women and their families in Daugavpils. Children were at particular risk of becoming infected with a disease due to non-compliance with hygiene standards in cramped apartments. The research is based on the material of medical reports of the Daugavpils Regional State Archives (LNA DZVA) of the Latvian National Archives of the Daugavpils City Skin and Venus Diseases Dispensary of the Latvian SSR (1953–1964), 916th fund, description no. 1, medical reports for the years 1947–1972. Fund 916 examines the problem of women’s transmission of sexually transmitted diseases in Soviet society during the study period in the Latvian SSR: factors influencing the spread of venereal diseases provoked by women’s prostitution, free sex and unprotected sex during this period of Soviet history. This trend is related to the low level of awareness of urban women.